2006
DOI: 10.1007/s10459-005-5492-1
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Attendance at Non-compulsory Lectures

Abstract: The General Medical Council in the UK recommends that undergraduate medical students be exposed to a variety of learning opportunities and increasingly take responsibility for their own learning. This study presents quantitative and qualitative data relating to attendance at non-compulsory plenary lectures in order to understand factors affecting the value placed by students on this component of the first 2 years of a contemporary medical curriculum. Attendance data were available for 87% first year and 78% se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 9 publications
8
53
1
Order By: Relevance
“…39,50 Our study data has demonstrated that multiple lectures in one day result in better attendance (median 72.9% and 52.6% for both multiple and single lectures in one day respectively). In addition to this, students agreed via our survey that they were unlikely to attend a single scheduled lecture.…”
Section: Students Are More Likely To Attend If They Have To Travel Lamentioning
confidence: 69%
See 4 more Smart Citations
“…39,50 Our study data has demonstrated that multiple lectures in one day result in better attendance (median 72.9% and 52.6% for both multiple and single lectures in one day respectively). In addition to this, students agreed via our survey that they were unlikely to attend a single scheduled lecture.…”
Section: Students Are More Likely To Attend If They Have To Travel Lamentioning
confidence: 69%
“…39,51 To tackle this problem university faculties should plan student-friendly timetables. 52 For example, non-attendance was higher on Mondays and Fridays in studies of health science students, but also in the wider student body.…”
Section: Students Are More Likely To Attend If They Have To Travel Lamentioning
confidence: 99%
See 3 more Smart Citations